GIS based chemical fate modeling : principles and applications - Pistocchi, Alberto, 1972- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
'This book covers the integration of chemical fate modeling for use in Geographic Information System (GIS) functions. It features a practical and hands-on approach that's intended for modelers preparing maps of chemical emissions, and creating landscape and climate properties within a GIS, while chemical fate calculations are performed using specialized model codes. A relevant part of the book also discusses data retrieval and processing as a basis for modeling. As such, the book offers a one-stop reference for practitioners who wish to integrate GIS with chemical modeling'--
'The book provides the fundamental knowledge necessary for the application of GIS in solving chemical fate modeling problems'--
Machine generated contents note: Foreword Chapter 1. Chemicals, models and GIS: a sort of introduction Chapter 2. Basics of chemical compartment models and their implementation with GIS functions Chapter 3. Basics of GIS operations Chapter 4. Map algebra Chapter 5. Distance calculations (with contributions by P. Mazzoli) Chapter 6. Spatial statistics and neighbourhood modeling in GIS Chapter 7. Digital elevation models, topographic controls and hydrologic modeling in GIS Chapter 8. Elements of dynamic modeling in GIS Chapter 9. Metamodeling and source-receptor relationship modeling in GIS Chapter 10. Spatial data management in GIS and the coupling of GIS and environmental models (by Ezio Crestaz) Chapter 11. Soft computing methods for the overlaying of chemical data with other spatially varying parameters (by Alberto Pistocchi, Davide Geneletti; with contributions by Paolo Mazzoli and Ezio Crestaz) Chapter 12. Types of data required for chemical fate modeling (by Alberto Pistocchi, Pilar Vizcaino, Christof J. Weissteiner) Chapter 13. Retrieval and analysis of emission data Chapter 14. Characterization of environmental properties and processes (by Alberto Pistocchi, Dimitar T. Marinov) Chapter 15. Complex models, GIS and data assimilation Chapter 16. The issue of monitoring data and the evaluation of spatial models of chemical fate Chapter 17. From Fate to exposure and risk modeling with GIS (by Stefano Bagli, Alberto Pistocchi) Chapter 18. GIS based models in practice: the Multimedia Assessment of Pollutant Pathways in the Environment (MAPPE) model (by Alberto Pistocchi, Dimitar T. Marinov) Chapter 19. Inverse modeling and its application to water contaminants (by Alberto Pistocchi, Dimitar T. Marinov) Chapter 20. Chemical fate and transport indicators and the modeling of contamination patterns Conclusions.
Includes bibliographical references and index.
Keywords: Environmental chemistry -- Geographic information systems; Transport theory -- Mathematical models